Biomimetic stem cell membrane-camouflaged iron oxide nanoparticles for theranostic applications. Issue 119 (17th November 2015) - Lai, Pei-Ying; Huang, Rih-Yang; Lin, Ssu-Yu; Lin, Yee-Hsien; Chang, Chien-Wen
Abstract : In this study, for the first time, stem cell membrane (STM)-camouflaged superparamagnetic iron oxide nanoparticles (SPIO NPs) were prepared and investigated for potential theranostic applications. Abstract : Superparamagnetic iron oxide nanoparticles (SPIO NPs) have been used extensively for various biomedical applications, such as magnetic resonance imaging (MRI), drug delivery, cellular tracking and magnetic hyperthermia therapy. Surface modifications of SPIO NPs are usually required to improve their rapid in vivo clearance profiles. In this study, we prepare novel stem cell membrane (STM)-camouflaged SPIO NPs for biomedical applications. The water-soluble and highly dispersed STM-SPIO NPs were prepared using a simple and mild sonication method. The increased size of STM-SPIO NPs compared to unmodified SPIO NPs suggested successful STM coating onto the SPIO NP surfaces. The STM coating was further confirmed by Transmission Electron Microscopy (TEM) imaging and dye retention assay. High preservation of STM-associated proteins on the SPIO NPs was verified by sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) analysis. Specifically, retention of stem cell-specific marker CD44 was confirmed using an antibody binding assay. As a potential MRI agent, STM-SPIO NPs exhibited good magnetization (65.9 emu g −1 ) and dose-dependent T2-weighted imaging contrasts ( R 2 = 653.3 s −1 mM −1 ) in vitro . In comparison to unmodified SPIO NPs, the macrophage uptake of STM-SPIO NPs was found to be significantly less by Prussian blue staining and Inductively Coupled Plasma Mass Spectrometry (ICP-MS) analysis. Under the application of an alternating magnetic field (AMF), STM-SPIO NPs successfully induced cancer cell death via a magnetic hyperthermia mechanism. The results demonstrated good potential for STM-SPIO NPs for future theranostic applications.